2014
DOI: 10.1177/0272989x14558424
|View full text |Cite
|
Sign up to set email alerts
|

Decision-making Processes among Prostate Cancer Survivors with Rising PSA Levels

Abstract: Background Prostate cancer survivors with a rising prostate specific antigen (PSA) level have few treatment options, experience a heightened state of uncertainty about their disease trajectory that might include the possibility of cancer metastasis and death, and often experience elevated levels of distress as they have to deal with a disease they thought they had conquered. Guided by self-regulation theory, the present study examined the cognitive and affective processes involved in shared decision making bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 33 publications
(57 reference statements)
0
12
0
Order By: Relevance
“…wanted detailed information shared about options [10]. In prostate cancer patients deciding between treatment and observation, patients identified the importance of the physician in making this decision [11]. There are few data on decision-making for patients with hematologic cancers.…”
Section: Discussionmentioning
confidence: 99%
“…wanted detailed information shared about options [10]. In prostate cancer patients deciding between treatment and observation, patients identified the importance of the physician in making this decision [11]. There are few data on decision-making for patients with hematologic cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Patients who suffered from a myocardial infarction and attributed their heart attack to bad habits reported more lifestyle and nutrition changes after 6 months (18). What is particularly relevant here is that such causal attributions are not only modifiable (19) but also susceptible to experimental manipulation: Ogden and Jubb (1) used vignettes that either emphasized psychological or biomedical causes of several diseases. They found that treatments that were congruent to the causes were considered to be more effective.…”
Section: Perceived Etiology and Type Of Treatmentmentioning
confidence: 99%
“…The quality of life for men treated for prostate cancer may be decreased, because standard treatment for prostate cancer involves removal of the prostate, which may cause incontinence or impotence, or "chemical castration" (the administration of hormones) which causes weight gain (cf. Shen et al 2015). These costs of screening would be invisible if five-year survival rates were used as a measure of the relative effectiveness of prostate cancer screening.…”
Section: The Science Of Cancer Prevention: Starting With Choice Of Enmentioning
confidence: 99%